Rumen fermentation, fatty acid profiles, meat quality and adipogenesis related gene expression of goat and sheep fed with high concentrated diet - Su, Candyrine Chui Len (2016)
The small ruminant (goats and sheep) industry in Malaysia can be described as slow growing as compared to the demand for the products. On the other hand, ruminant products are known to contain high amount of saturated fatty acids (SFA) which are often implicated as a source of modern-day diseases. To date, limited comparative studies have been carried out to characterize differences between goats and sheep, hence the two species are often assumed to be similar and thus raised and managed similarly. To meet the local demand, there is a need to improve the productivity of the small ruminant industry, by optimizing the growth protential of each animal species; and at the same time, to produce healthier meat and meat products. It is hypothesized that the feeding of high concentrate diet supplemented with linseed oil as a source of polyunsaturated fatty acids (PUFA), could improve the growth rate of the animals and at the same time, fortifying the meat and products with health beneficial PUFA. The primary objectives of this thesis were to co-compare rumen fermentation characteristics, growth performance, meat quality attributes and fatty acids profile in tissues of goat and sheep fed high concentrate fattening diet, with and without supplementation of PUFA; and to infer the differences in fatty acids profile due to the dietary treatments and animal species (goats vs sheep) through the expression of adipogenesis related genes. Three experiments were conducted to achieve the above objectives. In the first experiment, in vitro rumen fermentation characteristics in goats and sheep with or without PUFA added to the substrate were evaluated. Results showed superior fermentation characteristics in goats with higher in vitro gas production rate (P<0.001), accompanied by higher volatile fatty acids (VFA) production and in vitro organic matter digestibility (P<0.05). The higher population of total bacteria and two major cellulolytic bacteria (Ruminococcus albus and Butyrivibrio fibrisolvens) in goat compared to sheep also indicates higher digestive capability in goats. The addition of 4% linseed oil to the substrate did not show any negative effect on fermentation characteristics nor the VFA production, suggesting that the level oil was appropriate. Experiment 2 consisted of a 100-day feeding trial to determine the growth performance, digestibility and meat quality attributes of goats and sheep fed fattening diet with or without oil supplementation, in a 2 species x 2 diets factorial experiment with 6 animals (replicates) per treatment. Results of the study showed that irrespective of diet, sheep had better body weight gain (BWG) and feed efficiency (FE) compared to goats. Overall, supplementation of linseed oil at 29 g/day improved BWG by about 65 g/day (45% improvement over the control) and FE by 15% (5.01 vs 5.93). There was no species difference (except for crude protein) and no effect of dietary treatments on apparent digestibility. Goat meat had better quality attributes (P<0.001), including lower lipid oxidation and higher water holding capacity than sheep. Linseed oil supplementation did not affect meat lipid oxidation, indicating that the level of supplementation was appropriate. The fatty acids profile in various tissue, in vivo rumen fermentation and expression of adipogenesis related genes from the above feeding trial are reported in Chapter 5 with the objective of determining whether differences exist in fatty acids profile in goats and sheep fed similar diets and to elucidate the possible mechanisms for any differences exist. Results of the study showed that there were significant differences in the fatty acids profile in the longissimus dorsi (LD) muscle, subcutaneous (SC) fat and liver tissue between species and between dietary treatments. Although no species differences were observed in the total SFA, MUFA and PUFA content in the LD muscle, several individual fatty acids were significantly different between species, including higher n-3 PUFA in LD muscle of goats. Sheep had higher total SFA content but lower UFA in the SC fat and liver tissue. Linseed oil supplementation increased the linolenic acid content by 4.5 to 6.1 folds in the tissues samples analyzed suggesting oil supplementation provides a viable approach to enrich meat and ruminant products with essential PUFA. The result of the in vivo rumen fermentation characteristics explained for the differences in the fatty acids profile between species. The higher production of total VFA and acetic acid (primary precursor in fatty acid synthesis) in sheep suggest higher lipogenesis activity, and explained for the higher SFA content. The higher population of B. fibrisolvens in sheep than goats, which on the other hand had higher population of total methanogens and methanobacteriales, explained for the higher biohydrogenation intermediate in sheep. Relative expressions of adipogenesis related genes were used to elucidate the differences in the fatty acids profile between species and dietary treatment. The study found that, irrespective of diet, sheep had higher expression of fatty acid synthase gene (FASN) gene and also higher Acetyl- CoA carboxylase gene (ACACA) with oil supplementation. The higher expression of the above genes led to higher production of SFA content (especially palmitic acid) in the SC fat and liver tissue in sheep. Stearoyl-CoA desaturase (SCD) gene, which responsibles for the unsaturation of SFA, was lower in sheep than goats and was further downregulated with the addition of oil, which explains for the lower mono-unsaturated fatty acids (MUFA) content in sheep and in the oil supplemented group. On the other hand, peroxisome proliferator-activated receptor alpha (PPARα), which serves as the transcriptional factor for many lipogenic genes, is negatively correlated with ACACA and FASN genes. Therefore the downregulation of PPARα gene was accompanied by upregulation of ACACA and FASN genes in sheep and the opposite in goats, accounting for the different SFA production between species. Result of this thesis suggests that high concentrate feeding supplemented with PUFA (linseed oil at 4% level) is an applicable approach to improve the growth performance of small ruminants, and to produce healthier meat with beneficial fatty acids profile, without detrimental effect on rumen fermentation or meat quality attributes. Species differences in fatty acids profile were partly influenced by the various lipogenic genes expression and therefore, dietary manipulation of adipogenesis related genes expression (nutrigenomics) can be a useful tool especially in reducing the SFA content, in order to produce healthier ruminant meat and meat products.